Storm-related taphofacies and paleoenvironments of Malvinokaffric assemblages from the Lower/Middle Devonian in southwestern Gondwana - Horodyski, Rodrigo Scalise; Brett, Carlton E.; Sedorko, Daniel; Bosetti, Elvio Pinto; Scheffler, Sandro Marcelo; Ghilardi, Renato Pirani [UNESP]; Iannuzzi, Roberto (Elsevier, 2019)
Taphofacies of Malvinokaffric macroinvertebrate-bearing rocks from the uppermost Pragian to lower Givetian in southwestern Gondwana are evaluated. During the Lower/Middle Devonian, the Paraná Basin (southern Brazil) was positioned at high latitudes in southwestern Gondwana (60° to 80°S). Integrated litho- and taphofacies interpretations in siliciclastic environments presented here provide paleoecological and paleoenvironmental insights. The six taphofacies recognized here showed changing depositional conditions in paleoenvironments ranging from shoreface to offshore shelf settings. They vary in recurrence and abundance, but all facies exhibit evidence of storm events. Winter storms are to be expected at latitudes 60° to 80° S under cool climate zone. Storm-related taphofacies recurrence during the latest Pragian to early Givetian points to two agents of sedimentation, direct wave erosion by winter storms and sedimentary processes related to combined flow during deposition (e.g. turbidity currents and oscillatory flow). Winter storms are considered more capable of affecting sediment transport than hurricanes, due to longer duration and larger coverage area in higher latitudes. Therefore, winter storms of high latitudes should generate more persistent currents in space and time. Finally, the taphofacies, lithofacies and high-latitude paleogeographic context of the Paraná Basin suggest the action of storm-influence in the genesis of all Lower/Middle Devonian Malvinokaffric assemblages here recognized.
Keywords: Macroinvertebrates; Paleoclimatology; Paleogeography; Paleozoic; Taphonomy; Winter storms